Principles of Periocular Reconstruction following Excision of Cutaneous Malignancy - Scott M. Hayano; Katherine M. Whipple; Bobby S. Korn; Don O. Kikkawa (Journal of Skin Cancer)
Reconstruction of periocular defects following excision of cutaneous malignancy can present difficulties for oculofacial and reconstructive surgeons. The intricate anatomy of the eyelids and face requires precise restoration in order to avoid postoperative functional anesthetic concerns. Various reconstructive procedures based on common principles, location and size of the defect, can be applied to achieve restoration with the best possible functional and aesthetic outcomes.